Penerapan Metode Penemuan Terbimbing Dalam Meningkatkan Hasil Belajar Matematika Materi Perbandingan Dan Skala Pada Siswa Kelas V SDN Jangur Tahun Ajaran 2017/2018 Kecamatan Sumberasih Kabupaten Probolinggo - Rofikha Nuriyanti; ludfi arya wardana; galuh Lingga marta; Vifian lestin ferdina; siti fatimah (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
The problem on this class action research is caused by less optimal in process of mathematics teaching at SDN Jangur sumberasih sub-district Probolinggo regency which has implication in getting low results of learning mathematics especially on the comparison and scale study. This research aims to describe the implementation of guided discovery method in improving the results of learning mathematics in comparison and scale study on the students in grade 5 at SDN Jangur. The Research Methodology using qualitative approach with interactive descriptive method. The subject of the research include the headmaster and the teachers and students. The technique of data collection in this research using the observation, interview, and study of documentation. The results obtained from the research is the implementation of guided discovery method on the students at SDN Jangur that is be able to improve to be active, motivated and get interest in learning. It will increase the value of student learning that is from pre-action of the students’ average score that only got 55,25 and in frist cycle, the average score of student increase to be 72 then the average score is 83,9 in the second cycle. Therefore in the process of learning a teacher must be able to make the students active, motivated and has spirit in learning. One of the teachers can implement guided discovery method in learning process to make the students achieve the goal of learning that want to be achieved.